Treatment with long-acting lanreotide autogel in early infancy in patients with severe neonatal hyperinsulinism - Corda, Heike (Orphanet J Rare Dis, 2017)
BACKGROUND: Treatment of severe diffuse congenital hyperinsulinism (CHI) without sufficient response to diazoxide is complicated by the lack of approved drugs. Therefore, patients are often hospitalized long-term or have to undergo pancreatic surgery if episodes of severe hypoglycaemia cannot be prevented. A long-acting somatostatin analogue, octreotide, has been reported to be an effective treatment option that prevents severe hypoglycaemia in children with CHI, and its off-label use is common in CHI. However, octreotide requires continuous i.v. or s.c. infusion or multiple daily injections. Here, we report our experiences with the use of a monthly application of a long-acting somatostatin analogue, lanreotide autogel® (LAN-ATG), in early infancy. RESULTS: The mean blood glucose concentration within 7 days before the first LAN-ATG administration were compared to 7 days after the first LAN-ATG administration and increased by 0.75 mmol/L (range 0.39–1.19 mmol/L). In the following weeks intravenous glucose infusions, octreotide, and glucagon treatment could be successfully stopped in all patients 3–20 days after the first LAN-ATG injection without substantial worsening of the hypoglycaemia rate. Increased carbohydrate requirements could be normalized with an average reduction in the carbohydrate-intake of 7 g/kg body weight/d (range 1.75–12.8 g/kg body weight/d). Over a total of 52 treatment months, no serious adverse effects occurred. CONCLUSION: Long-term LAN-ATG treatment improved blood glucose concentrations, lowered the frequency of hypoglycaemia or allowed for normalization of oral carbohydrate intake in infants with CHI younger than 6 months of age. No severe side effects were observed. LAN-ATG might be an alternative treatment option in infants with severe CHI who lack risk factors for necrotizing enterocolitis and are not responding to current treatment regimens as an alternative to surgery after careful individual evaluation.